1993
DOI: 10.1002/aoc.590070102
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and organometallic chemistry of cyclophosphazenes and polyphosphazenes

Abstract: This review describes the chemistry of cyclophosphazene and poiyphosphazene iigand systems and their transition and organometallic complexes. The structures of the ligands and the complexes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 86 publications
4
64
0
1
Order By: Relevance
“…Although a considerable number of cyclotriphosphazenes are known [27][28][29][30][31][32][33][34][35][36] those of Ti [36] are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Although a considerable number of cyclotriphosphazenes are known [27][28][29][30][31][32][33][34][35][36] those of Ti [36] are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR spectra of the spiro compounds, (3), (5) and (8), are complex multiplets with similar chemical shifts (Table 1), whereas those for the mono-ansa moieties in compounds (4) and (6) are observed as two complex multiplets and for the non-gem cis bis-ansa compound (7) as four complex multiplets. Although analysis of these multiplets, in principle, could lead to 3 J(FH) and 3 J(PH) magnitudes and a conformational analysis of the spiro and ansa rings, in practice, this is not feasible because the appropriate Karplus-type relations for 3 J(FH) and 3 J(PH) magnitudes in such cyclophosphazene derivatives are not known.…”
Section: Introductionmentioning
confidence: 96%
“…Bridged compounds became important for reactions of (1) with di-amines of increasing chain length (n = 4, 5) [3] and with chain lengths n >5 only bridged compounds were reported by Guerch et al [4]. On the other hand, only ansa derivatives were obtained with structurally rigid di-functional reagents such as the di-lithium derivatives of ferrocene, ruthenocene and dibenzylchromium [5][6][7][8]. Herberhold and co-workers [9] reported that the reactions of the Li salt of the ferrocene (fc) diol with cyclophosphazenes, (1) and N 3 P 3 F 6 (9), gave ansa derivatives, but only spiro-derivatives were obtained when the Li salts of the di-thiol or di-selenol ferrocene were used as reagents, in spite of the larger linking atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] The cyclophosphazenes behave as poor donors towards metal ions, unless electron-releasing moieties, such as alkyl or amino, are present in their molecule. In contrast to the numerous well-characterised complexes of some amino-or alkyl-substituted cyclotetraphosphazenes, complexes of relatively basic cyclophosphazenes, possessing heterocyclic nitrogen base moieties in their molecule were less investigated.…”
Section: Introductionmentioning
confidence: 99%